Adolescent and parents toolkit (adapt) - self managing psychological concerns of an epilepsy diagnosis: phase 1 consumer involvement. (24th May 2012) - Brown, A; Talbot, E; Simpson, T; Whitehouse, W
Abstract : Aim: A large body of literature exists documenting the psychological impact for young people and their family members, when diagnosed with epilepsies. Psychosocial interventions to address this have particularly focused on self management group work approaches. However, studies have had limited success. This may be because insufficient preparatory work was done to develop interventions or assess the preferences for delivery methods. This report describes the consumer involvement exercise to develop toolkits to aid young people and their family members self manage the emotional side of an epilepsy diagnosis. Methods: A mixed methodology approach for data collection was employed. Focus group participants consisted of young people aged 13-17 years with a diagnosis of epilepsy (n=14) and their parents (n=23). Issues for inclusion in the toolkit were also ascertained by questionnaires (young people n=84 and parents n=114). Results: A sizeable majority of respondents recognised the emotional concerns attached to a diagnosis of epilepsy (67% young people and 77% parents) and the need for help and support (53% young people and 83% parents). 63% young people and 83% parents said they would read a toolkit if available (figures 1, 2 and 3 ). Conclusions: The data demonstrates the need for self management toolkits that deliver psychologically based approaches for both prevention and brief intervention work. A feasibility study is needed and is currently being planned to further develop and implement the toolkits in practice.